Insecticidal and oviposition deterrent properties of some spices against coleopteran beetle, Sitophilus oryzae - Devi, Kalpana C. (Springer-Verlag, 2011)
Eighteen spices were screened for their insecticidal potential and antiovipositional properties against the rice weevil- Sitophilus oryzae—a serious insect pest of stored food grains. The bioefficacy of the powders and hexane extracts of selected spices were determined by assessing the toxicity, effect on F(1) progeny, contact toxicity, persistence and seed viability. Responses varied with the spices, dosage and exposure time. Powders of mace and pepper, at 1% level were highly effective resulting in total mortality of S. oryzae by one week followed by nutmeg and clove with 100% mortality and cinnamon and star anise with 90% mortality at 5% concentration. These spices also completely inhibited F(1) progeny. The hexane extracts of these spices at 1,000 ppm showed insecticidal activity, with pepper extract recording 100% mortality by 5 days. S. oryzae was susceptible to clove oil resulting in 92% mortality. Mortality was 51.63% in nutmeg, 66.6% in cinnamon, and 79.8% in case of mace and star anise. Hexane extracts of star anise, cinnamon and clove at 0.59 μl/cm(2) on filter paper discs induced 100% mortality by 72 h. These spices offered protection to wheat up to 9 months without affecting seed germination thereby showing promise as grain protectants.